Re-Evaluasi Dan Masa Depan Hubungan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
The involvement of the International Monetary Fund (IMF) in Indonesia was intended to assist Indonesia's economy in getting back on track after the 1997 financial crisis. The Government of the Republic of Indonesia has sent its lastest Letter of Intent (Lol) and Memorandum of Economic and Financial Policies (MEFP). The aim of this research was to answer the following questions. Why Indonesia was agreeable to accepting the IMF's suggestions and how the relationships between Indonesia and the IMF in the future after the end of the Lol and MEFP would be. The research was conducted by documentary and library study with a legal comparative approach. It revealed that Indonesia was subordinate to the IMF. This unequal relationships has caused unequal agreements between them. Indonesia has been dependent on the IMF since 1997 until the end of 2003. Having decided not to extend the current IMF's special program later, this State would no longer be eligible for the Paris Club of donors for rescheduling. It had become independent in its relationships with the IMF since the beginning of 2004